RESTRUKTURISASI SEBAGAI UPAYA PENINGKATAN KINERJA ANAK-ANAK PERUSAHAAN PT RAJAWALI NUSANTARA INDOENSIA DALAM LINGKUNGAN INDUSTRI GULA - , Yassir Ismail ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Being able to compete in today's business competition requires every business person to move quickly through increasing business competitiveness. In order to meet such demands, the company needs a strategy adapted to the company's current position and future. PT Rajawali Nusantara Indonesia is one of the largest State-Owned Enterprises (SOEs), which has promising growth potential and is supported by a large asset ownership, human resources with adequate knowledge, and potential future business development, need to make strategic moves in an attempt to reach toward the optimal development and growth. PT RNI is a company in the form of Holding Company, the parent company that owns stakes in several subsidiaries in order to control the management and operations of those subsidiaries. PT RNI is currently engaged in three core businesses are: agribusiness, trade and pharmaceuticals. Particularly in the agribusiness sector consists of the sugar industry, the oil palm industry and the tea industry. Currently subsidiaries of PT RNI engaging in the sugar industry are PT PG Rajawali I, PT PG Rajawali II, and PT PG Candi Baru. The purpose of this study is to evaluate the right strategy for PT RNI with the portfolio management business which generates synergies especially for the sugar industry in order to to distinguish should it stay as separate entities or is merged into one company.